The effect of cooling rate during multiple reflow soldering on intermetallic layer of Sn-4.0 Ag-0.5Cu/ENImAg - M.A., Rabiatul Adawiyah; A.B., M. Hafiz; O., Saliza Azlina; J., Zolhafizi; W.M., Wan Nur Azrina; O., Shahrul Azmir (Wiley-VCH Verlag, 2019)
The effect of intermetallic compound layer between Sn-4.0 Ag-0.5Cu solder bump and electroless nickel/immersion silver (ENImAg) surface finish under different cooling rate during multiple reflow condition was investigated. The results show that the interfacial (Cu, Ni)6Sn5 intermetallic compound were formed at the early stage after the first reflow process. After multiple reflow processes, both (Cu, Ni)6Sn5 and (Ni, Cu)3Sn4 appeared as needle-shaped at interface due to the amount of copper concentration into a solder balls. The spalling intermetallic compound of (Cu, Ni)6 Sn5 was spotted in the solder which was caused by the formation of needle-shaped from the gaps of (Cu, Ni)6Sn5. The intermetallic compound thickness and grain sizes became thicker and coarser with increasing reflow time, respectively. The results also perceived that the cooling rate condition can influence the growth of intermetallic compound formation. Faster cooling rate produced thinner intermetallic layer as well as smaller grain sizes compared to slow cooling rate. Hence, the cooling rate is a necessary parameter in the solder reflow process because it has an impact on the microstructure of morphology and intermetallic growth.